Brazil : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2012)
The paper discusses the stability of Brazil's financial system, which is diversified and shows sustained economic progress. Fiscal and monetary policies have been aimed to improve bank reserves, and foreign exchange intervention has been streamlined to curb volatility in the exchange market. These measures have been effective in achieving the immediate targets, maintaining macroeconomic stability, and ensuring adequate financial sector buffers. However, there are indications of emerging strains in some sectors and asset classes.